Remediation of Acidic Soil with Mission Grass (Pennisetum polystachion) Grounds - Khamis, Aidee Kamal (2024)
Lime (CaCO3) application is the most common practice to neutralise soil acidity prior to planting. However, the effectiveness of liming depends on its reactivity and interactions with various soil types. Therefore, mission grass (Pennisetum polystachion; PP) grounds have been proposed as an alternative for soil acidity remediation, owing to their rapidly decomposable residue and release of basic cations. This study evaluated the ability of PP to increase the pH and the relationship between pH and redox potential (Eh) in loamy soil and sandy soil. The addition of 2.5% (w/w) CaCO3 rapidly increased the pH in loamy soil but gradually decreased the pH in sandy soil, with a value of 7.30 and 7.50, respectively, on day 20. The addition of 2.5% (w/w) PP increased the pH in loamy soil and sandy soil to 5.60 and 6.50, respectively, on day 20. The Eh value in loamy soil was significantly lower after the addition of PP compared with CaCO3 (+50.0 mV and + 200.0 mV, respectively). In sandy soil, the addition of PP produced a lower Eh value on day 20 compared with the addition of CaCO3. The fluctuating Eh values in both soil types were associated with soil moisture, electrical conductivity and organic matter and should be measured systematically with pH. The addition of PP was beneficial in slowly increasing the soil pH over time, thus influencing the favourable reducing condition as indicated by the lower Eh values. The application of PP as an alternative and a complement to the conventional liming practice should be further studied to reduce the adverse impacts on the soil to establish a balance between agricultural productivity and sustainable agriculture.